2021
DOI: 10.3390/ijms22052333
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Macrophages in Immune System Dysfunction under Real and Simulated Microgravity Conditions

Abstract: In the process of exploring space, the astronaut’s body undergoes a series of physiological changes. At the level of cellular behavior, microgravity causes significant alterations, including bone loss, muscle atrophy, and cardiovascular deconditioning. At the level of gene expression, microgravity changes the expression of cytokines in many physiological processes, such as cell immunity, proliferation, and differentiation. At the level of signaling pathways, the mitogen-activated protein kinase (MAPK) signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 102 publications
1
19
0
1
Order By: Relevance
“…Our results show that pro-inflammatory TNF-α secretion by macrophage cells in simulated microgravity was significantly decreased across all three phenotypes evaluated. This agrees with current literature on the downregulation of TNF-α protein expression by macrophages in microgravity [ 11 ]. A review of literature highlights the differences in results seen across studies, with some studies reporting increases in TNF-α expression [ 55 , 56 , 57 ] and others reporting decreases [ 5 , 19 , 20 , 21 ] from µG, suggesting that the variety of cell types, microgravity system, duration, and methods used could be contributing factors [ 10 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results show that pro-inflammatory TNF-α secretion by macrophage cells in simulated microgravity was significantly decreased across all three phenotypes evaluated. This agrees with current literature on the downregulation of TNF-α protein expression by macrophages in microgravity [ 11 ]. A review of literature highlights the differences in results seen across studies, with some studies reporting increases in TNF-α expression [ 55 , 56 , 57 ] and others reporting decreases [ 5 , 19 , 20 , 21 ] from µG, suggesting that the variety of cell types, microgravity system, duration, and methods used could be contributing factors [ 10 ].…”
Section: Discussionsupporting
confidence: 93%
“…Published data on the effect of altered gravity on macrophages have not extensively considered the role of macrophage phenotypes. Macrophage microgravity studies in general have shown variable results and are relatively limited [ 10 , 11 ]. Overall, macrophages demonstrate many sensitivities to changes in gravity, both in their short- and long-term responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Sun et al [23] reviewed the current knowledge about the dysfunction of macrophages exposed to µg and discussed the mechanisms of these abnormal responses.…”
Section: Breast Cancer Cells In Microgravity: New Aspects For Cancer Researchmentioning
confidence: 99%
“…[20] Influence of gravitational changes on proliferative processes and calcium homeostasis. [13] In addition, the SI covers five reviews (Table 2) [10,[22][23][24][25]. These 16 excellent papers were published as detailed in Tables 1 and 2.…”
mentioning
confidence: 99%